Peran Manajemen SDM Strategis, Integritas Anggota, Kualitas Pelatihan, dan Keadilan Organisasi terhadap Efektivitas Reformasi Polri - Ginting, Donald Happy; Earlyanti, Novi Indah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The reform of the Indonesian National Police (Polri) is a national strategic agenda aimed at improving professionalism, accountability, and the overall quality of public services. The success of this reform is not solely dependent on structural or regulatory changes but is strongly influenced by internal organizational factors such as strategic human resource management (HRM), member integrity, training quality, and perceptions of organizational justice. This study analyzes the contributions of these four variables to the effectiveness of Polri’s reform by employing a literature review method based on research published within the last decade. The findings reveal that strategic HRM plays a crucial role in establishing transparent, objective, and competency-based personnel development systems. Member integrity serves as a moral foundation that guides professional behavior and prevents the misuse of authority. Moreover, high-quality training aligned with operational demands enhances officers’ technical skills, discipline, and adaptability in addressing modern security challenges. Perceived organizational justice significantly influences motivation, job satisfaction, and officers’ commitment to institutional reform. Overall, these variables interact and collectively strengthen an organizational culture rooted in ethics, competence, and accountability. The study concludes that the success of Polri’s reform cannot be achieved solely through structural adjustments but requires a profound transformation in human resource management as the fundamental pillar of institutional improvement.